(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: To identify independent factors associated with postpartum hemorrhage following vaginal delivery at Hai Phong Obstetrics and Gynecology Hospital, 2020-2026. Methods: A 1:2 matched case-control study using retrospective medical record review, comprising 61 postpartum hemorrhage cases and 122 controls matched by maternal age, residence, parity, and gestational age. Conditional logistic regression was applied; results expressed as adjusted odds ratios (aOR) with 95% confidence intervals. Results: 4 independent factors were significantly associated with postpartum hemorrhage: macrosomia > 4000g (aOR = 15.42; 95% CI: 3.21-74.1; p = 0.001), polyhydramnios (aOR = 12.65; 95% CI: 1.48-108.2; p = 0.020), history of postpartum hemorrhage (aOR = 10.12; 95% CI: 1.65-62.0; p = 0.012), and anemia hemoglobin < 110 g/L (aOR = 3.14; 95% CI: 1.45-6.82; p = 0.004). Conclusion: 4 independent risk factors were identified with direct applicability for developing postpartum hemorrhage risk screening tools and active prevention protocols.